Pemikiran Imam Al Ghazali Dalam Kitab Minhajul Muta'allim dan Imam Badruddin Ibnu Jamaah Dalam Kitab Tadzkiratus Sami Wal Mutakallim Fi Adabil Alim Wal Muta'allim tentang Adab Menuntut Ilmu - Irfan, Ahmad; Ayuhan, Ayuhan; Basit, Abdul; Johan, Budi; Riyadi, Didi Ageng; Setiyadi, Dicky (Tadarus Tarbawy : Jurnal Kajian Islam dan Pendidikan, 2024)
The issue of delinquency among students is regrettable, as it deviates from the objectives of education, especially Islamic education. Islamic education, as the cornerstone of character development, becomes an important factor to examine in order to find solutions. This research was conducted using a qualitative method with a comparative analysis between two literatures, namely Minhajul Muta’allim by Imam Al-Ghazali and Tadzkiratussami’ Wal Mutakallim Fi Adabil Alim Wal Muta'allim  by Imam Badruddin Ibnu Jamaah. The study found that the character traits that should be developed in the world of education include purifying the soul, honoring the teacher, having good character towards oneself, and exhibiting good character towards the subject matter. All of these elements are essential to internalize Islamic values into the students' lives.